A8.18 Tissue specific pro-drug for the next generation of anti-TNF therapy in rheumatoid arthritis. (13th February 2015) - Ferrari, M; Onuoha, SC; Sblattero, D; Pitzalis, C
Abstract : Background and objective: Despite the obvious success of current anti-TNFα agents in Rheumatoid Arthritis (RA) treatment, high number of non-responders and systemic adverse effects (e.g. reactivation of tuberculosis) highlight the need of broader efficacy and improved safety profiles. Recently the importance of angiogenesis in the progression of arthritis has been unveiled. Angiogenesis can be exploited for tissue selective drug delivery approaches to drive in-situ drug accumulation, reducing systemic side effects. Towards this end we developed a bispecific antibody pro-drug platform with ICAM1 specificity to deliver an anti-TNFα payload to the arthritic tissue, allowing anti-TNFα activation selectively in the arthritic synovium and avoiding systemic TNFα engagement. Materials and methods: The anti-ICAM1 variable region was subcloned in fusion with the anti-TNFα antibody Adalimumab in dual variable domain (DVD) bispecific format. The linker between the outer and inner variable domain was engineered to be short and bear an MMP1 cleavable site, forming an activatable DVD (aDVD) antibody. Reactivity with RA human synovium was determined using immunohistochemistry on tissue sections. MMP1-mediated antibody activation was tested using RA synovial fluids and RA synovial fibroblasts. Activity and biological functionality of the anti-TNFα moiety was assessed in-vitro using ELISA, Biacore and L-929 TNFα-cytotoxicity assays. Results: The aDVD bispecific antibody was able to maintain synovial microvascular targeting, conveyed by the anti-ICAM1 variable domain, in RA synovial tissue sections. The intact molecule however, showed a reduced capacity to bind TNFα with 500-fold affinity decrease caused by steric hindrance of the outer variable region. Digestion with physiologically relevant concentrations of MMP1 was sufficient to restore 100% anti-TNFα activity (EC50 53 pM), comparable to the parent Adalimumab antibody (49 pM). Further, the un-processed aDVD antibody was significantly impaired in rescuing the L-929 cell line from TNFα-induced cytotoxicity. Digestion with MMP1 and activation of the anti-TNFα domain restored the anti-TNFα biological activity with an IC50 of 0.1 nM comparable to Adalimumab IgG (IC50 0.1 nM). Conclusions: Our results demonstrate the development of a synovium-specific pro-drug delivery system for RA. The impaired TNFα binding capacity of the intact molecule ensures a decreased systemic TNFα engagement. Presence of metalloproteinases in RA synovium would activate and deliver the anti-TNFα activity locally in the site of disease. This strategy may allow greater therapeutically-relevant doses to be delivered in the synovium, increasing pharmacological potency, allowing reduction in the dosage and/or administration frequency, with the ultimate goal of reducing systemic exposure, achieve better therapeutic index and decreasing healthcare costs.